Preventive detention under internal security act 1960 and dangerous drugs (special preventive measures) act 1985; a comparison of procedural safeguards / Elias Yusri Zamri, Fithril Hakim Ab Jalil, Mohd Fakharuddin Ikhwan Mohd Nasir. - Zamri, Elias Yusri; Ab Jalil, Fithril Hakim; Mohd Nasir, Mohd Fakharuddin Ikhwan (2008)
Preventive detention laws are given in virtue of Article 149 of the Federal Constitution. Article 149 of the Constitution provides for the powers to legislate laws against subversion and threats to the national security. The focus of this research is to discuss the procedural safeguard of the Internal Security Act 1960 (ISA) and the Dangerous Drugs (Special Preventive Measures) Act 1985 (SPMA). In Malaysia, ISA has been wielded most visibly in response to alleged security fears. The ISA is an expansive law but it is its provision for indefinite detention without trial to which the State has most frequent resort: the first sixty days of this detention are typically at the initiation of police authorities, and subsequent two-year periods occur at the authorization and renewal of the Minister of Home Affairs. Similarly, SPMA provides for detention without trial to be valid in combating the threat of drug abuse in consideration to the public interest. This research will point out the strength of this Act to be implemented in the ISA. This research will compare and contrast the two Acts in terms of the procedural safeguards given to the detainees. It is important as to clarify that this research will note that the weaknesses in ISA should be implemented by a better procedural safeguard given in the SPMA. Recommendations and opinions from scholars and experts are provided in this research to improve the procedural safeguard in ISA.